PENGARUH GURU DAN TEMAN SEBAYA TERHADAP PENDIDIKAN AKHLAK SISWA DI MTS NEGERI 2 KOTA BENGKULU - Febi Nina Barokah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
This study to determine whether there is a significant influence of positive teachers  and peers against moral education students In MTs Negeri 2 Kota Bengkulu. This research  uses quantitative approach. The population is all students of class VI MTs Negeri 2 Kota Bengkulu.  Sampling  is done  by purposive sampling  that is determination technique with certain consideration. Data were analyzed  by using simple and double  linear regression  test.The result of this research  shows that there is a significant influence  between  teacher  toward  moral education of VII MTS Negeri 2 Kota Bengkulu  academic year 2016/2017 is 30.7%, while the rest 69.3%  is influenced  by other  variables  besides  teacher  variables.  There  is a significant influence  between  peers to moral education of students  is 10.3%  and There is a significant influence between  teachers  and peers to moral education of students  by 55.6%  while the remaining 44.4%  dipegaruhi by variables other than teacher  variables and peers